2020
DOI: 10.1089/end.2020.0382
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Microwave Ablation of Stage T1b Renal Cell Carcinoma: Short-Term Assessment of Technical Feasibility, Short-Term Oncologic Outcomes, and Safety

Abstract: Purpose: To report on the safety, technical results, and oncologic outcomes of computed tomography guided percutaneous microwave ablation of stage cT1b renal cell carcinoma. Materials and Methods: This single-center retrospective study investigated consecutive patients with T1b renal cell carcinoma who were treated with CT guided percutaneous microwave ablation between December 2015 and May 2019. Patient baseline characteristics, tumor biologic features, technical parameters, clinical outcomes, and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…CA appeared to be the most used ablation tool with 6/9 studies and 204/311 (66%) patients. Only Shapiro et al [12] and Guo et al [15] reported results with MWA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CA appeared to be the most used ablation tool with 6/9 studies and 204/311 (66%) patients. Only Shapiro et al [12] and Guo et al [15] reported results with MWA.…”
Section: Discussionmentioning
confidence: 99%
“…MWA relies on the continuous realignment of polar molecules (primarily water) with the oscillating microwave field, increasing kinetic energy and tissue temperature [30,31]. Two included studies used microwaves: Shapiro et al [12] and Guo et al [15]. Sixty-three patients received this treatment.…”
Section: Ablation Methodsmentioning
confidence: 99%
See 3 more Smart Citations